2019
DOI: 10.3390/nu11092076
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Variation of Vitamin K Status According to Vkorc1 Point Mutations Using Rat Models

Abstract: Vitamin K is crucial for many physiological processes such as coagulation, energy metabolism, and arterial calcification prevention due to its involvement in the activation of several vitamin K-dependent proteins. During this activation, vitamin K is converted into vitamin K epoxide, which must be re-reduced by the VKORC1 enzyme. Various VKORC1 mutations have been described in humans. While these mutations have been widely associated with anticoagulant resistance, their association with a modification of vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Moreover, several factors influence serum under-carboxylated osteocalcin levels notably osteoblastic synthesis, hormonal status, renal function, age, sex, timing of blood sampling, and specificity of the radioimmunoassay (185)(186)(187). Recently, a study showed that under-carboxylated osteocalcin increases in resistant rodents under vitamin K deficient diet (188). But currently there is no link between osteocalcin and chronic AR exposure effects.…”
Section: Other Vitamin K-dependent Proteinsmentioning
confidence: 99%
“…Moreover, several factors influence serum under-carboxylated osteocalcin levels notably osteoblastic synthesis, hormonal status, renal function, age, sex, timing of blood sampling, and specificity of the radioimmunoassay (185)(186)(187). Recently, a study showed that under-carboxylated osteocalcin increases in resistant rodents under vitamin K deficient diet (188). But currently there is no link between osteocalcin and chronic AR exposure effects.…”
Section: Other Vitamin K-dependent Proteinsmentioning
confidence: 99%